Assessing Non-English Teachers’ Pedagogical Content Knowledge (PCK) in Teaching English at Preschools - Nurlela; Alemina Br Perangin-angin; Nasution, Ely Hayati; Nasution, Vivi Adriyani (Linguistik, Terjemahan, Sastra (LINGTERSA), 2023)
This paper aimed to assess non-English teachers’ Pedagogical Content Knowledge (PCK) in teaching English at preschools. Ten (10) teachers with varied degrees were treated as the object of the study. A four-month training, involving a pretest, face-to-face tutorial, micro-teaching, and post-test, supported by recording, observation, questionnaire, and interview, was conducted to evaluate the teachers’ PCK progress. The results indicated that non-English Teachers’ PCK progressed significantly after the treatments. It was concluded that non-English graduates were good at teaching English at preschools in terms of teaching a concept, yet they had limitations in developing practical skills.